2020
DOI: 10.1007/s12015-020-10037-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and its Therapeutics: Special Emphasis on Mesenchymal Stem Cells Based Therapy

Abstract: The novel virus, Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) caused the Corona Virus Disease-2019 (COVID-19) outbreak in Wuhan, Hubei province of China. This virus disseminated rapidly and reached to an unprecedented pandemic proportion in more than 213 nations with a large number of fatalities. The hypersecretion of pro-inflammatory cytokines is the main cause of mortality and morbidity due to COVID-19, therefore strategies that avert the cytokine storm may play a crucial role in abating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 120 publications
(94 reference statements)
0
17
0
Order By: Relevance
“…It has been suggested that AMPs that destroy the envelope glycoprotein can be used to stop or disrupt the life cycle of SARS-CoV-2 [ 287 ]. AMPs, which are found in the secretion of mesenchymal stem cells (MSCs), have antimicrobial properties, the ability to attenuate cytokine storms, and, therefore are an attractive approach to prevent the COVID-19 pandemic [ 288 ].…”
Section: Prediction and Development Of New Ampsmentioning
confidence: 99%
“…It has been suggested that AMPs that destroy the envelope glycoprotein can be used to stop or disrupt the life cycle of SARS-CoV-2 [ 287 ]. AMPs, which are found in the secretion of mesenchymal stem cells (MSCs), have antimicrobial properties, the ability to attenuate cytokine storms, and, therefore are an attractive approach to prevent the COVID-19 pandemic [ 288 ].…”
Section: Prediction and Development Of New Ampsmentioning
confidence: 99%
“…The concept of cell therapy for the treatment of CF lung infection and inflammation is complex, particularly with the dynamic nature of the “drug” in the form of macrophages, hMSCs or both ( Hodges and Conlon, 2019 ). Fortunately, cell-based approaches have been described in other diseases such as alveolar proteinosis ( Suzuki et al, 2014 ), Niemen Pick disease ( Schuchman and Desnick, 2017 ) acute respiratory distress syndrome ( Horie et al, 2018 ), interstitial pulmonary fibrosis ( Bonfield and Caplan, 2010 ), bronchopulmonary dysplasia ( Cerny et al, 2008 ), rheumatoid arthritis ( Jorgensen, 2010 ) and others ( Lachmann et al, 2014 ; Morrison et al, 2017 ; Khoury et al, 2020 ; Verma et al, 2020 ). Bone marrow supplementation or hMSC therapy is not corrective longitudinally, but would enhance the capacity of patients to manage their own immune environment.…”
Section: Discussionmentioning
confidence: 99%
“…The above review provides not only new knowledge about the molecular mechanisms of stem cells pro-regenerative action, clinical trials based on the use of MSCs with complete status ( Gov, 2020a , Gov, 2020b , Gov, 2020c , Gov, 2020d , Gov, 2020e ), but also summarizes the so far published knowledge on the use of stem cells in the treatment of SARS-CoV-2 infection ( Chen, 2020 , Khatri et al, 2018 , Waszak et al, 2012 , Li et al, 2016 , Li et al, 2020 , Chan et al, 2016 , Curley et al, 2017 , Lee et al, 2011 , Weiss and Dahlke, 2019 , Harrell et al, 2020 , Harrell et al, 2019 , Costela-Ruiz et al, 2020 , Tan et al, 2020 , Raza and Khan, 2020 , Krasnodembskaya et al, 2010 , Johnson et al, 2017 , Chow et al, 2020 , Sutton et al, 2016 , Cotter et al, 2012 , Van Linthout et al, 2011 , Thanunchai et al, 2015 , Wu et al, 2018 , ClinicalTrials.gov, 2020 , Connick et al, 2012 , Wilson et al, 2014 , Saleh et al, 2020 , Inamdar and Inamdar, 2013 , Walter et al, 2014 , Anjos-Afonso et al, 2004 , Shetty, 2020 , Liang et al, 2020 , Sengupta et al, 2020 , Hassanpour et al, 2020 , Akbari and Rezaie, 2020 , Tsuchiya et al, 2020 , SĂĄnchez-Guijo et al, 2020 , Chen et al, 2020 , Foronjy et al, 2014 , Metcalfe et al, 2015 , Metcalfe, 2020 , Shu et al, 2020 , Irmak et al, 2020 , Bonifazi et al, 2020 , Lee, 2018 , Musiał-Wysocka et al, 2019 , Verma et al, 2020 , Lukomska et al, 2019 ), and also effects of SARS-CoV-2 infection on lung epithelial stem cells ( …”
Section: Discussionmentioning
confidence: 99%
“…The first side effects in the form of the disease may occur in the first month after the transplant ( Bonifazi et al, 2020 ). Further, clinical studies have shown that bone marrow MSCs with a potential profibrogenic potential can cause liver fibrosis ( Lee, 2018 , Musiał-Wysocka et al, 2019 , Verma et al, 2020 ). The available data also show the growth of neoplastic tumors such as lung cancer, breast cancer, prostate cancer, gastric cancer and colon cancer ( Lee, 2018 , Musiał-Wysocka et al, 2019 , Verma et al, 2020 ).…”
Section: Stem Cells Therapy For Covid-19mentioning
confidence: 99%
See 1 more Smart Citation